PP21 Can paramedics correctly recognise cardiac arrhythmias and does recency of training have an impact?. Issue 10 (28th September 2017) - Sharp, Alex
Abstract : Background: Paramedics increasingly utilise alternative care pathways and direct referrals to reduce Emergency Department admissions. The National Institute of Clinical Effectiveness (NICE) Transient Loss of Consciousness (TLoC) guidelines are one such example, with questions previously raised on the ability of paramedics to identify the arrhythmias. Studies identify that paramedics can safely recognise ST segment Myocardial Infarctions, however there remains a lack of evidence around arrhythmia recognition. This study aims to identify if paramedics can identify key arrhythmias and whether the recency of training impacts on recognition. Method: A quasi-experimental methodology was adopted for the study using a bespoke website. Paramedics were shown 20 12-lead ECGs of key arrhythmias. Each ECG appeared on the screen for a maximum of 60 s. During this time the paramedic was directed to identify the arrhythmia within a free text box, before proceeding to the next arrhythmia. Results: 356 paramedics consented into the study with 230 completing the study. The majority completing the study were standard paramedics [73.04%, n=168], with alternate paramedic roles such as critical care paramedics and paramedic practitioners making up the remainder The mean recognition rate was 47.03% [95% CI 43.82–50.22] with individual paramedics ranging from 10% to 95% and a median recognition rate of 45%. Recognition of individual arrhythmias ranged from 94.78% [95% CI 91.91–97.65] for Atrial Flutter to 3.91% [95% CI 1.4–6.42] for Prolonged QTc. No statistical difference was demonstrated between participants who had received training within the past two years and those who had not (47.96% vs. 46.19%, p=0.59). Conclusion: This study identified a wide variation in the ability of paramedics to recognise arrhythmias with no obvious patterns identified. The results of the study indicate that the current lack of arrhythmia recognition within paramedic training and curriculum guidance needs to be addressed.